2014
DOI: 10.1136/tobaccocontrol-2014-051563
|View full text |Cite
|
Sign up to set email alerts
|

Passive exposure to electronic cigarette (e-cigarette) use increases desire for combustible and e-cigarettes in young adult smokers

Abstract: Background Passive exposure to combustible cigarette use has been shown to act as a cue to increase smoking urge. Given the resemblance of e-cigarettes and other electronic nicotine delivery systems (ENDS) to combustible cigarettes, we examined whether these devices could also act as a cue to increase smoking desire and urges in those passively exposed. Methods Young adult daily smokers (age 18–35 years; N=60) completed subjective ratings before and after exposure to a study confederate drinking bottled wate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
80
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(90 citation statements)
references
References 22 publications
7
80
1
2
Order By: Relevance
“…The relationship of alcohol and marijuana use to recent e-cigarette use is particularly noteworthy, given the heated debate in the tobacco control field about the degree of harm and potential addiction liability associated with e-cigarettes (Chatham-Stephens et al, 2014;Glynn, 2014;King, Smith, McNamara, Matthews, & Fridberg, 2014;Niaura, Glynn, & Abrams, 2014;Siegel, 2014). One recent cross-sectional population-based study has already shown that individuals who use e-cigarettes are high on certain mental health vulnerability factors known to predict smoking persistence and cessation failure (Cummins, Zhu, Tedeschi, Gamst, & Myers, 2014).…”
Section: Discussionmentioning
confidence: 97%
“…The relationship of alcohol and marijuana use to recent e-cigarette use is particularly noteworthy, given the heated debate in the tobacco control field about the degree of harm and potential addiction liability associated with e-cigarettes (Chatham-Stephens et al, 2014;Glynn, 2014;King, Smith, McNamara, Matthews, & Fridberg, 2014;Niaura, Glynn, & Abrams, 2014;Siegel, 2014). One recent cross-sectional population-based study has already shown that individuals who use e-cigarettes are high on certain mental health vulnerability factors known to predict smoking persistence and cessation failure (Cummins, Zhu, Tedeschi, Gamst, & Myers, 2014).…”
Section: Discussionmentioning
confidence: 97%
“…Among adult smokers, seeing someone use an e-cigarette in vivo or in video adverts increases the desire and urge to smoke tobacco cigarettes18 19 and decreases intentions to abstain from smoking tobacco cigarettes among former smokers 20…”
Section: Introductionmentioning
confidence: 99%
“…One study found that exposing young adult daily smokers to e-cigarette use by others in an experimental setting increased their desire to smoke combustible and e-cigarettes (41).…”
Section: Toxicitymentioning
confidence: 99%